Insight into the Antioxidant Activity of 1,8-Dihydroxynaphthalene Allomelanin Nanoparticles - Alexandra Mavridi-Printezi; Fabio Mollica; Rosa Lucernati; Marco Montalti; Riccardo Amorati (MDPI AG, 2023)
Melanins are stable and non-toxic pigments with great potential as chemopreventive agents against oxidative stress for medical and cosmetic applications. Allomelanin is a class of nitrogen-free melanin often found in fungi. The artificial allomelanin obtained by the polymerization of 1,8-dihydroxynaphthalene (DHN), poly-DHN (PDHN), has been recently indicated as a better radical quencher than polydopamine (PDA), a melanin model obtained by the polymerization of dopamine (DA); however, the chemical mechanisms underlying this difference are unclear. Here we investigate, by experimental and theoretical methods, the ability of PDHN nanoparticles (PDHN-NP), in comparison to PDA-NP, to trap alkylperoxyl (ROO•) and hydroperoxyl (HOO•) radicals that are involved in the propagation of peroxidation in real conditions. Our results demonstrate that PDHN-NP present a higher antioxidant efficiency with respect to PDA-NP against ROO• in water at pH 7.4 and against mixed ROO• and HOO• in acetonitrile, showing catalytic cross-termination activity. The antioxidant capacity of PDHN-NP in water is 0.8 mmol/g (ROO• radicals quenched by 1 g of PDHN-NP), with a rate constant of 3 × 105 M−1 s−1 for each reactive moiety. Quantum-mechanical calculations revealed that, thanks to the formation of a H-bond network, the quinones in PDHN-NP have a high affinity for H-atoms, thus justifying the high reactivity of PDHN-NP with HOO• observed experimentally.